Desenvolvimento de sistemas de informação no Ministério Público Federal: problemas e propostas de solução - Araújo, Cleber de (2017)
This research intended to understand the human, cultural and political aspects, preponderant and difficult in the Information Systems (IS) development processes in the Ministério Público Federal (MPF), with the specific objectives of mapping the problems that can cause loss of productivity and effectiveness in IS development, its categorization, the identification of root problems and the proposition of actions for improvements in the process. The study aimed to generate new perspectives regarding the development of software with better quality for MPF and public institutions that have similar characteristics. Conversation with specialists was the instrument used to obtain data and information. Qualitative approach was adopted in this work, because the participants showed themselves active and each research object was treated in a differentiated way, from the design, obtaining and transcribing of data and information, as well as planning, for the accomplishment of the analysis and proposing improvements. Because of the expectation of practical application of found results, from theoretical and technical references, the applied dimension is studied. Due to the way in which the information was investigated, it is an actionresearch, since the researcher acted in a cyclical way, in the tasks of planning, recording and evaluating results, until the desired results are achieved. From the transcripts of the talks, the information was interpreted based on the technique of content analysis, seeking representativeness, homogeneity, relevance and exclusivity. After, suggestions for improvement were presented, with proposals for prioritizing actions and restrictions of the present study with suggestions for new research. At the end, the following applied technical product was obtained: Process for standards establishment in Information Systems development from Ministério Público Federal, whose content is inserted in Management of Operations in the Public Sector research line.